An IoT-enabled monitoring and control system for electrochromic smart windows - Hsien-Hern Koay; Gregory Soon How Thien; Benedict Wen-Cheun Au; Abdelrahman Hamed Ebrahem Abdelhamed; Ruthramurthy Balachandran; Zi-Neng Ng; Kah-Yoong Chan (Discover Internet of Things)
Abstract Electrochromic (EC) smart windows are highly efficient in preventing solar irradiation. Nevertheless, an insufficient automated monitoring and control system for EC windows has been observed. This study outlined the framework for designing a control system that effectively regulated the voltage polarity of an EC smart window. Integrating Internet of Things (IoT) capabilities and environmental sensors enhanced the smart window control system. This integration allowed for automated monitoring and adjustment of light intensity (below and above 30,000 lx), temperature (below and above 32 °C), and UV index (below 3 and above 7) for the smart window. The magnitude of the current supplied from the output load of the operational circuit module was directly correlated with the switching time of the electrochromic window. Moreover, voltage fluctuation was observed during the evaluation testing of the control system, which was ascribed to the reliability of the breadboard platform. This study also provided a functional design analysis for a Wi-Fi-enabled control system, presented insights into manual and automatic control modes under diverse environmental conditions, and improved user interaction through real-time data visualization using the IoT Blynk platform. Overall, this study presented a range of cost-effective approaches for managing the dynamic EC window using Wi-Fi and sensor-enabled technology.